Phylogenetic analysis of the human gut microbiota using 16S rDNA clone libraries and strictly anaerobic culture-based methods - Hayashi, Hidenori; Sakamoto, Mitsuo; Benno, Yoshimi (Microbiology and immunology, 2002)
The human gut microbiota from three healthy subjects were compared by the use of a sequence analysis of 16S rDNA libraries and a culture-based method. Direct counts ranged from 1.9 X 10" to 4.0 X 10" cells/g (wet weight), and plate counts totaled 6.6 X 10(10) to 1.2 X 10(11) CFU/g (wet weight). Sixty to seventy percent of the bacteria in the human intestinal tract cannot be cultured with currently available methods. The 16S rDNA libraries from three subjects were generated from total community DNA in the intestinal tract with universal primer sets. Randomly selected clones were partially sequenced. All purified colonies detected from the surface of the agar plate were used for a partial sequencing of 16S rDNA. On the basis of sequence similarities, the clones and colonies were classified into several clusters corresponding to the major phylum of the domain Bacteria. Among a total of 744 clones obtained, approximately 25% of them belonged to 31 known species. About 75% of the remaining clones were novel "phylotypes" (at least 98% similarity of clone sequence). The predominant intestinal microbial community consisted of 130 species or phylotypes according to the sequence data in this study. The 16S rDNA libraries and colonies included the Bacteroides group, Streptococcus group, Bifidobacterium group, and Clostridium rRNA clusters IV, IX, XIVa, and XVIII. Moreover, several previously uncharacterized and uncultured microorganisms were recognized in clone libraries and colonies. Our results also showed marked individual differences in the composition of intestinal microbiota.